Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Ex 4.4

Ex 4.4, 1

Ex 4.4, 2

Ex 4.4, 3 Important

Ex 4.4, 4 Important You are here

Ex 4.4, 5

Ex 4.4, 6 Important

Ex 4.4, 7

Ex 4.4, 8

Ex 4.4, 9

Ex 4.4, 10 Important

Ex 4.4, 11 Important

Ex 4.4, 12

Ex 4.4, 13

Ex 4.4, 14 Important

Ex 4.4, 15 Important

Ex 4.4, 16

Ex 4.4, 17 (MCQ) Important

Ex 4.4, 18 (MCQ) Important

Chapter 4 Class 12 Determinants

Serial order wise

Last updated at June 11, 2023 by Teachoo

Ex 4.4, 4 Verify A (adj A) = (adj A) A = |𝐴|I for A = [■8(1&−1&2@3&0&−2@1&0&3)] Calculating |𝑨| |A| = |■8(1&−1&2@3&0&−2@1&0&3)| = 1 |■8(0&−2@0&3)| – (–1) |■8(3&−2@1&3)| +2 |■8(3&0@1&0)| = 1 (0 – 0) + 1 (9 + 2) +2 (0 – 0) = 11 Calculating adj A adj A = [■8(A_11&A_21&A_31@A_12&A_22&A_32@A_13&A_23&A_33 )] A = [■8(1&−1&2@3&0&−2@1&0&3)] M11 = |■8(0&−2@0&3)| = 0(3) – 0(–2) = 0 M12 = |■8(3&−2@1&3)| = 3(3) – 1(–2) = 11 M13 = |■8(3&0@1&0)| = 3(0) – 0(1) = 0 M21 = |■8(−1&2@0&3)| = −1(3) – 0(2) = −3 M22 = |■8(1&2@1&3)| = 1(3) – 1(2) = 1 M23 = |■8(1&−1@1&0)| = 1(0) – 1(−1) = 1 M31 = |■8("−" 1&2@0&"−" 2)| = -1(–2) – 0(2) = 2 M32 = |■8(1&2@3&−2)| = 1(–2) – 3(2) = –8 M33 = |■8(1&−1@3&0)| = 1(0) – 3(−1) = 3 Now, A11 = (–1)1 + 1 M11 = (–1)2 0 = 0 A12 = (–1)1+2 M12 = (–1)3 (11) = –11 A13 = (–1)1+3 M13 = (–1)4 0 = 0 A21 = (–1)2+1 M21 = (–1)3 (−3) = 3 A22 = (–1)2+2 M22 = (–1)4 . 1 = 1 A23 = (–1)2+3 M23 = (–1)5 (1) = −1 A31 = (–1)3+1 M31 = (–1)4 (2) = 2 A32 = (–1)3+2 M32 = (–1)5 (–8) = 8 A33 = (–1)3+3 M33 = (–1)6 (3) = 3 Thus adj (A) = [■8(A11&A21&A31@A12&A22&A32@A33&A23&A33)] = [■8(0&3&2@−11&1&8@0&−1&3)] Calculating A (adj A) [■8(1&−1&2@3&0&−2@1&0&3)] [■8(0&3&2@−11&1&8@0&−1&3)] = [■8(1(0)−1(⤶7−11)+2(0)&1(3)−1(1)+2(−1)&1(2)−1(8)+2(3)@3(0)+0(⤶7−11)+(−2)(0)&3(3)+0(1)+(−2)(−1)&3(2)+0(8)+(−2)(3)@1(0)+0(⤶7−11)+3(0)&1(3)+0(1)+3(−1)&1(2)+0(8)+3(3))] = [■8(0+11+0&3−1−2&2−8+6@0−0−0&9+0+2&6+0−6@0−0+0&3+0−3&2+0+9)] = [■8(11&0&0@0&11&0@0&0&11)] = 11 [■8(1&0&0@0&1&0@0&0&1)] = 11I Calculating (adj A)A [■8(0&3&2@−11&1&8@0&−1&3)] [■8(1&−1&2@3&0&−2@1&0&3)] = [■8(0(1)+3(3)+2(1)&0(−1)+3(0)+2(0)&0(2)+3(−2)+2(3)@−11(1)+1(3)+8(1)&−11(−1)+1(0)+8(0)&−11(2)+1(−2)+8(3)@0(1)+(−1)(3)+3(1)&0(−1)+(−1)(0)+3(0)&0(2)+(−1)(−2)+3(3))] = [■8(0+9+2&−0+0+0&0−6+6@−11+3+8&11+0+0&−22−2+24@0−3+3&−0−0+0&−0+2+9)]a = [■8(11&0&0@0&11&0@0&0&11)] = 11 [■8(1&0&0@0&1&0@0&0&1)] = 11I Calculating |A| I |A|I = 11I Thus, A (adj(A)) = (adj A) A = |A| I = 11I Hence Proved